2005
DOI: 10.1007/s11240-004-9159-z
|View full text |Cite
|
Sign up to set email alerts
|

Histology of embryogenic responses in soybean anther culture

Abstract: In order to clarify the embryogenic responses in soybean anther culture, anthers of four cultivars were cultured under known conditions to trigger androgenic response. A histological study was performed with anthers in vivo and with approximately 100 explants sampled after 9, 12, 15, 18, 21, 30 and 45 days of culture. In vitro culture triggered the frequent accumulation of phenolic compounds on the locular and anther surfaces, and also caused the destruction of cells and tissues in complex structure such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…According to the authors, the globular structures were originated from subepidermal cell divisions in the cotyledonary mesophyll. Nevertheless, in a detailed histological study in soybean anther culture, somatic embryogenesis of unicellular origin was observed from the epidermis and the middle layer, and of multicelluar origin from connective calluses (Rodrigues et al, 2005). The basal cell divided anticlinally, forming two derived cells which through periclinal divisions, formed two series of suspensor-resembling cells, where the apical cell was maintained as initial ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, the globular structures were originated from subepidermal cell divisions in the cotyledonary mesophyll. Nevertheless, in a detailed histological study in soybean anther culture, somatic embryogenesis of unicellular origin was observed from the epidermis and the middle layer, and of multicelluar origin from connective calluses (Rodrigues et al, 2005). The basal cell divided anticlinally, forming two derived cells which through periclinal divisions, formed two series of suspensor-resembling cells, where the apical cell was maintained as initial ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In soybean, histological sections of de novo formed embryogenic structures can be found in some reports (Barwale et al, 1986;Finer and McMullen, 1991;Kiss et al, 1991;Liu et al, 1992;Sato et al, 1993). However, a characterization of the different developmental stages of soybean somatic embryos was performed only by Christou andYang (1989), Fernando et al (2002), and Rodrigues et al (2005). In this study, we analyzed different soybean somatic embryos in order to characterize ontogenetic routes followed by these embryos by means of histological approaches.…”
Section: Introductionmentioning
confidence: 96%
“…Addition of 2,4-D in the medium and culturing in light significantly increased the morphogenic response of anther walls and connective tissues. No androgenic response was observed in anther culture of four soybean genotypes but somatic embryogenesis was observed from the epidermis and the middle layer (Rodrigues et al, 2004(Rodrigues et al, , 2005. Higher concentration of 2,4-D during anther culture results in plasmolysis of microspores.…”
Section: Soybean Tissue Culture Strategiesmentioning
confidence: 90%
“…The proembryo resembled the Embryo-Like Structure (ELS) in soybean anther culture (Rodrigues et al 2005). Proembryo composed of embryogenic cells characterized by high nucleus to cytoplasm ratio, high starch and protein reserves (Fig.…”
Section: Calli Cultured In Liquid Mediummentioning
confidence: 99%